Processing technology of down-proof down jacket fabric
By synthesizing modified 1-aminopyrene and modified graphene composites under nitrogen protection, and combining them with modified polyurethane and modified iron tetraoxide nanoparticles, electrospinning and thermal bonding technology were used to prepare drill-proof down jacket fabrics, which solved the problems of insufficient drill-proof, waterproof and breathable properties and mechanical strength of existing fabrics, and achieved efficient drill-proof and waterproof and breathable effects.
Patent Information
- Application Number
- CN202510067006.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing down jacket fabric needs to be improved in terms of drill-proof, waterproof and breathable properties and mechanical strength, which leads to drill-proof problems during the production and use of down jackets, which affects the appearance and wearing experience.
Using a processing technology of anti-drill down jacket fabric, fabrics with high anti-static, hydrophobic and mechanical strength are prepared by synthesizing modified 1-aminopyrene and modified graphene composites under nitrogen protection, and combined with modified polyurethane and modified iron tetraoxide nanoparticles.
It significantly improves the anti-drilling performance, waterproof and breathable properties and mechanical strength of down jacket fabric, reduces the risk of drilling down jackets during use, while retaining good breathability and comfort.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric processing, and in particular to a processing technology for down-drilling-proof down jacket fabric. Background Art
[0002] Down is a natural protein fiber with the characteristics of being light, thin and warm. It is one of the natural raw materials with the best thermal insulation performance. Down-filled textiles have become popular in daily life, especially down jackets in winter have become an indispensable daily necessity. Down jackets have always been loved by consumers due to their softness, comfort, good warmth retention and lightness. With the continuous improvement of living standards, the requirements for down jackets have gradually become higher. However, due to various reasons, down jackets will have the problem of down drilling during the production and use process, which not only seriously affects its overall appearance, but the drilled down will also affect the consumer's wearing experience.
[0003] In the prior art, due to its unique dendritic protein molecular structure, the down in the down jacket is easily charged by friction, resulting in the phenomenon of like charges repelling each other, increasing the risk of down leaking from the micropores or seams of the fabric. In order to improve the anti-down drilling performance of the down jacket fabric, conductive materials are usually added during the fabric manufacturing process to improve the conductivity of the fabric, so as to eliminate the influence of static electricity on the down drilling of the down jacket;
[0004] However, the dispersion of conductive substances in the fabric substrate and the degree of cross-linking with the molecules of the fabric substrate are poor, resulting in the need to further improve the mechanical strength of the conductive fabric. Down jackets are relatively fluffy, and the fabric is easily rubbed against the outside world when worn, causing damage to the fabric structure and increasing the risk of down drilling. Moreover, conductive materials have poor hydrophobicity, and after being added to the fabric, they affect the fabric's waterproof and breathable properties. The processed fabric is difficult to have both anti-down drilling and waterproof and breathable properties.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a processing technology for anti-down drilling down jacket fabric, which is used to solve the technical problem that the anti-down drilling down, waterproof and breathable performance and mechanical strength of the down jacket fabric in the prior art need to be further improved.
[0007] The object of the present invention can be achieved by the following technical scheme: A processing technology for anti-drilling down jacket fabric, comprising the following steps;
[0008] S1. Under nitrogen protection, place isocyanate propyl triethylsilane, toluene and 1-aminopyrene in a three-necked flask at a temperature of 50-60°C, keep the temperature for reaction for 1-2 hours, and then post-treat to obtain modified 1-aminopyrene;
[0009] The reaction principle for preparing modified 1-aminopyrene is:
[0010] 1-Aminopyrene contains an amino group. In the presence of an isocyanate group, the lone pair of electrons on the nitrogen atom of the amino group can undergo a condensation reaction with the isocyanate group to generate modified 1-aminopyrene modified with isocyanatepropyltriethylsilane.
[0011] S2, placing graphene, modified 1-aminopyrene and ethanol in a three-necked flask heated to 50-60°C, stirring for 20-30 minutes, adding sodium hydroxide solution to the three-necked flask, keeping the temperature for reaction for 90-120 minutes, post-treating, and obtaining modified graphene;
[0012] The reaction principle for preparing modified graphene is:
[0013] The silicon-oxygen bonds in the modified 1-aminopyrene are hydrolyzed to generate silanols, which react with active functional groups on the surface of graphene to generate chemical bonds, thereby generating modified graphene modified with the modified 1-aminopyrene.
[0014] S3, placing N,N-dimethylformamide, modified graphene and modified ferroferric oxide nanoparticles in a three-necked flask, heating to 100-110°C, ultrasonically dispersing for 20-30 minutes, adding sodium hydroxide solution to adjust the pH to 8±0.2, keeping the temperature for reaction for 0.5-1 hour, and post-treating to obtain a modified graphene composite;
[0015] The reaction principle for preparing the modified graphene composite is:
[0016] Under weak alkaline conditions, the epoxy groups of the modified ferroferric oxide nanoparticles undergo a ring-opening condensation reaction with the hydroxyl groups of the modified graphene to form covalent crosslinks to generate a modified graphene composite modified by the modified ferroferric oxide nanoparticles.
[0017] S4, placing the modified graphene composite, modified polyurethane and N,N-dimethylformamide in a three-necked flask, ultrasonically dispersing for 1-2 hours, and electrospinning to obtain a fabric lining film;
[0018] S5. The base fabric is used as the outer layer and the fabric lining film is used as the inner layer. A modified cross-linking agent is coated between the two layers, and the layers are placed in a hot melt bonding machine for thermal bonding to obtain a down-proof down jacket fabric.
[0019] Furthermore, in step S1, the usage ratio of isocyanatepropyltriethylsilane, toluene and 1-aminopyrene is 1-2g:250-300mL:1-2g, and the post-treatment step comprises: after the reaction is completed, the temperature of the three-necked flask is increased to 75-85°C, and toluene is evaporated under reduced pressure to obtain modified 1-aminopyrene.
[0020] Furthermore, in step S2, the concentration of the sodium hydroxide solution is 0.1-0.2 mol / L, the amount ratio of the graphene, modified 1-aminopyrene, ethanol and sodium hydroxide solution is 2-3 g: 1-5 g: 250-300 mL: 30-50 mL, and the post-treatment step includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain modified graphene.
[0021] Furthermore, in step S3, the concentration of the sodium hydroxide solution is 3-3.5 mol / L, the amount ratio of the N,N-dimethylformamide, the modified graphene and the modified ferrosoferric oxide nanoparticles is 100-150 mL: 1-2 g: 1-2 g, and the post-treatment includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain a modified graphene composite.
[0022] Furthermore, in step S4, the usage ratio of the modified graphene composite, modified polyurethane and N,N-dimethylformamide is 0.5-1g:2-5g:50-100mL; in step S5, the base fabric is composed of nylon fiber and cotton fiber blended in a blending ratio of 20-30:70-80, the hot pressing process temperature of thermal bonding is 120-150°C, the hot pressing time is 30-40S, and the hot pressing pressure is 1.5-2.0MPa.
[0023] Furthermore, the preparation method of the modified ferroferric oxide nanoparticles is as follows: placing ferroferric oxide nanoparticles, acetone and KH-560 in a three-necked flask, heat-dispersing for 3-4 hours, centrifuging, washing the precipitate with acetone for 2-3 times, and drying to obtain the modified ferroferric oxide nanoparticles.
[0024] The reaction principle for preparing modified ferroferric oxide nanoparticles is:
[0025] The siloxy groups in KH-560 undergo a condensation reaction with the hydroxyl groups on the surface of the ferroferric oxide nanoparticles to generate stable siloxy bonds, thereby obtaining KH-560-modified modified ferroferric oxide nanoparticles.
[0026] Furthermore, the usage ratio of the ferrosoferric oxide nanoparticles, acetone and KH-560 is 2-3 g: 50-60 mL: 0.5-1 g.
[0027] Furthermore, the preparation method of the modified polyurethane comprises the following steps:
[0028] A1. Place acetone and dibutyltin dilaurate in a three-necked flask, heat to 70-80°C, and keep the temperature for reaction for 1-2 hours to obtain a catalyst solution for later use;
[0029] A2, 1-thioglycerol, tridecafluorooctyl methacrylate, acetone and dimethylphenylphosphine borane are placed in a three-necked flask, heated to 50-60°C, and stirred for 5-6 hours to obtain a fluorine-containing monomer;
[0030] The synthetic reaction equation of fluorinated monomers is:
[0031]
[0032] The synthetic reaction mechanism of fluorinated monomers is:
[0033] The thiol hydroxyl group in 1-thioglycerol has strong nucleophilicity and can attack the methacrylate double bond in tridecafluorooctyl methacrylate to obtain a fluorinated monomer containing a hydrophobic carbon fluoride chain.
[0034] The mass spectrometry analysis data of the fluorinated monomers were: 540.03 (100.0%), 541.04 (16.6%), 542.03 (4.5%), 542.04 (2.2%).
[0035] A3. Place isophorone diisocyanate, polyethylene glycol and acetone in a round-bottom flask, disperse them by ultrasonic for 30-60 minutes, add them dropwise to the catalyst solution, add fluorinated monomer and 2-hydroxyethyl disulfide, and react at the temperature for 2-3 hours to obtain modified polyurethane.
[0036] Furthermore, in step A1, the amount ratio of acetone to dibutyltin dilaurate is 20-30mL:0.1-0.5g; in step A2, the volume ratio of 1-thioglycerol, tridecafluorooctyl methacrylate, acetone and dimethylphenylphosphine borane is 0.05-0.1:0.05-0.1:20-30:0.05-0.1; in step A3, the amount ratio of isophorone diisocyanate, polyethylene glycol, acetone, catalyst solution, fluorine-containing monomer and 2-hydroxyethyl disulfide is 0.1-0.5g:0.1-0.5g:50-100mL:20-30mL:2-5mL:0.1-0.5g.
[0037] The synthetic reaction equation of modified polyurethane is:
[0038]
[0039]
[0040] Wherein: “*” represents the active connection site of the organic chain segment.
[0041] The synthetic reaction mechanism of modified polyurethane is:
[0042] Isophorone diisocyanate reacts with the alcoholic hydroxyl group of polyethylene glycol under the catalysis of dibutyltin dilaurate to generate carbamate, and a fluorinated monomer and 2-hydroxyethyl disulfide are added. The remaining isocyanate in isophorone diisocyanate reacts with the alcoholic hydroxyl group of the fluorinated monomer and 2-hydroxyethyl disulfide to generate a modified polyurethane containing a dynamic disulfide bond by chain extension.
[0043] Furthermore, the preparation method of the modified crosslinking agent comprises the following steps: placing polypropylene glycol, epichlorohydrin and boron trifluoride etherate in a three-necked flask, heating to 50-60° C., stirring for 2-5 hours, adding sodium hydroxide solution, keeping warm and stirring for 2-6 hours, and post-treating to obtain the modified crosslinking agent.
[0044] The synthetic reaction equation of the modified cross-linking agent is:
[0045]
[0046] The synthetic reaction principle of the modified cross-linking agent is:
[0047] Boron trifluoride ether acts as a Lewis acid catalyst, and its electron pair is transferred from the oxygen atom to the epoxy group in epichlorohydrin, making the epoxy group positively charged and enhancing its electrophilicity. The alcoholic hydroxyl group of polypropylene glycol is negatively charged and acts as a nucleophilic reagent to attack the carbon atom of epichlorohydrin, and the epoxy group is opened to form an ether bond. Sodium hydroxide solution is added to provide an alkaline environment, and the hydroxyl group of chloropropanol is deprotonated to form an alkoxy anion. The alkoxy anion attacks the chlorinated carbon in the molecule, and nucleophilic substitution occurs. The chloride ion leaves to obtain a modified cross-linking agent.
[0048] Furthermore, the volume ratio of the polypropylene glycol, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution is 5-10:10-20:0.3-0.5:40-60, the concentration of the sodium hydroxide solution is 1.5-2 mol / L, and the post-treatment step comprises: cooling the reaction liquid to room temperature, extracting with ethyl acetate solution for 3 times, taking the upper layer liquid for low-pressure rotary evaporation to obtain a modified cross-linking agent, and the ethyl acetate solution is composed of pure water and ethyl acetate in a volume ratio of 1:1.
[0049] The present invention has the following beneficial effects:
[0050] 1. The anti-drilling down jacket fabric prepared by the present invention comprises modified graphene composite, modified polyurethane and deionized water being ultrasonically dispersed into a spinning solution, and an inner lining film of the fabric is obtained by electrospinning. The inner lining film of the fabric is used as an inner layer, and the base fabric is used as an outer layer. A modified crosslinking agent is coated between the two layers, and the layers are placed in a hot melt bonding machine for thermal bonding to obtain the anti-drilling down jacket fabric. The fluorine-containing monomer in the modified polyurethane is synthesized by a thiol-ene click reaction of tridecafluorooctyl methacrylate and 1-thioglycerol catalyzed by dimethylphenylphosphine borane. It becomes a monomer containing a large number of carbon-fluorine bonds. The carbon-fluorine bonds have strong hydrophobicity, which increases the hydrophobicity of the anti-down drilling down fabric. The modified polyurethane is composed of hard segments and soft segments, and has good flexibility itself, which is beneficial to the migration of large molecular chain segments. The addition of 2-hydroxyethyl disulfide introduces disulfide bonds through chain extension. Under the action of heat and light, the thiol group can form disulfide bonds with another thiol group again as the molecular chain moves, and cross-linking can be achieved. The wear of the down jacket fabric during use can be repaired, and the anti-down drilling performance of the down jacket fabric can be improved.
[0051] 2. The anti-down drilling down jacket fabric prepared by the present invention has a modified graphene composite composed of modified graphene and modified ferroferric oxide nanoparticles added during the electrospinning process. Graphene is a two-dimensional material composed of a single layer of carbon atoms and has good electrical conductivity, which improves the anti-static ability of the anti-down drilling down jacket fabric. The static electricity accumulation of the down jacket fabric will cause charges to be generated on the surface of the fabric, attracting the down to move to the surface of the fabric, so the improvement of the anti-static ability can also improve the anti-down drilling performance of the down jacket fabric. The modified ferroferric oxide nanoparticles and the modified graphene are connected by chemical bonds to form a coating, which together with 1-aminopyrene and isocyanatepropyltriethylsilane improves the dispersibility of graphene in the electrospinning solution. At the same time, the fluorinated side chains of the modified polyurethane form a hydrophobic force, which strengthens the force between the polyurethane and various fillers, so that the damaged down jacket fabric can not only restore the surface integrity, but also repair its conductive properties and hydrophobic properties, thereby further improving the anti-down drilling property of the down jacket fabric.
[0052] 3. The anti-down drilling down jacket fabric prepared by the present invention is coated with a modified cross-linking agent between the inner layer and the outer layer during heat bonding. The modified cross-linking agent uses boron trifluoride etherate as a ring-opening catalyst and sodium hydroxide solution provides an alkaline environment to promote the synthesis of the modified cross-linking agent. The modified cross-linking agent undergoes a ring-opening reaction with the hydroxyl groups of the base fabric and the hydroxyl groups in the modified polyurethane to form ether bonds, thereby improving the adhesion between the fabric lining film and the base fabric and increasing the tensile strength of the down jacket fabric. At the same time, the fabric lining film manufactured by electrospinning technology has a thinner diameter and a high specific surface area, which can fill the fiber gaps, reduce the down drilling phenomenon while retaining the breathability of the down jacket fabric. DETAILED DESCRIPTION
[0053] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] This embodiment provides a processing technology for anti-drilling down jacket fabric, comprising the following steps:
[0056] S1. Preparation of modified graphene composite
[0057] Weigh: 2 g of ferroferric oxide nanoparticles, 50 mL of acetone and 0.5 g of KH-560 in a three-necked flask, incubate and disperse for 3 h, centrifuge, wash the precipitate with acetone for 3 times, dry to obtain modified ferroferric oxide nanoparticles, and set aside;
[0058] Weigh: Under nitrogen protection, place 250 mL of toluene, 1 g of 1-aminopyrene and 1 g of isocyanatopropyltriethylsilane in a three-necked flask at 50°C, keep warm for 2 hours, and after the reaction is completed, raise the temperature of the three-necked flask to 85°C, evaporate toluene under reduced pressure, and obtain modified 1-aminopyrene;
[0059] Weigh: 2 g of graphene, 1 g of modified 1-aminopyrene and 250 mL of ethanol, place in a three-necked flask heated to 55°C, stir for 30 min, add 30 mL of 0.2 mol / L sodium hydroxide solution to the three-necked flask, keep warm for 90 min, after the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until neutral and then drain, transfer the filter cake to a drying oven at 80°C, and vacuum dry to constant weight to obtain modified graphene;
[0060] Weigh: 100 mL of N,N-dimethylformamide, 1 g of modified graphene and 1 g of modified ferroferric oxide nanoparticles, place them in a three-necked flask, heat to 100°C, ultrasonically disperse for 20 min, add 3 mol / L sodium hydroxide solution to adjust the pH to 8.01, and keep warm for 1 h. After the reaction, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 70°C, and vacuum dry to constant weight to obtain a modified graphene composite.
[0061] S2. Preparation of modified polyurethane
[0062] Weigh: 20 mL of acetone and 0.1 g of dibutyltin dilaurate, put them in a three-necked flask, heat to 80°C, keep warm for 2 hours to obtain a catalyst solution, and set aside;
[0063] Weigh: 0.05 mL of 1-thioglycerol, 0.05 mL of tridecafluorooctyl methacrylate, 20 mL of acetone and 0.05 mL of dimethylphenylphosphine borane in a three-necked flask, heat to 60° C., and stir for 6 h to obtain a fluorine-containing monomer;
[0064] Weigh: 0.1 g of isophorone diisocyanate, 0.1 g of polyethylene glycol and 50 mL of acetone into a round-bottom flask, ultrasonically disperse for 50 min, add dropwise into 20 mL of the catalyst solution, add 2 mL of fluorinated monomer and 0.1 g of 2-hydroxyethyl disulfide, and react at this temperature for 2 h to obtain a modified polyurethane.
[0065] S3. Preparation of modified crosslinking agent
[0066] Weigh: 200 mL of ethyl acetate and 200 mL of pure water, mix evenly to obtain ethyl acetate solution, set aside;
[0067] Weigh: 5 mL of polypropylene glycol, 10 mL of epichlorohydrin and 0.3 mL of boron trifluoride etherate are placed in a three-necked flask, heated to 60°C, stirred for 3 h, added with 40 mL of 1.5 mol / L sodium hydroxide solution, kept warm and stirred for 6 h, and the reaction liquid was cooled to room temperature, extracted with ethyl acetate solution for 3 times, and the upper liquid was taken for low-pressure rotary evaporation to obtain a modified cross-linking agent.
[0068] S4. Preparation of anti-drilling down jacket fabric
[0069] Weigh: 0.5 g of modified graphene composite, 2 g of modified polyurethane and 50 mL of N,N-dimethylformamide into a three-necked flask, and ultrasonically disperse for 2 h to obtain a spinning solution for later use;
[0070] The spinning solution was placed in a 100 mL syringe after being allowed to stand to remove bubbles. A needle with an inner diameter of 0.75 mm and an outer diameter of 1 mm was selected as the spinning needle. Tin foil was attached to the drum as a receiving layer. The electrospinning voltage was set to 15 kV, the perfusion speed was set to 2 mL / h, the perfusion volume was set to 10 mL, the drum speed was set to 400 r / min, and the distance between the needle and the receiver was 12 cm. After the spinning was completed, the fabric lining film was obtained by drying.
[0071] The TC cloth is used as the outer layer, the fabric lining film is used as the inner layer, a modified cross-linking agent is coated between the two layers, and the layers are put into a hot-melt adhesive machine to obtain the down-penetration-proof down jacket fabric.
[0072] Example 2
[0073] This embodiment provides a processing technology for anti-drilling down jacket fabric, comprising the following steps:
[0074] S1. Preparation of modified graphene composite
[0075] Weigh: 2.5 g of ferroferric oxide nanoparticles, 55 mL of acetone and 0.7 g of KH-560 in a three-necked flask, incubate and disperse for 3 h, centrifuge, wash the precipitate with acetone for 3 times, dry to obtain modified ferroferric oxide nanoparticles, and set aside;
[0076] Weigh: Under nitrogen protection, place 270 mL of toluene, 1.5 g of 1-aminopyrene and 1.5 g of isocyanatopropyltriethylsilane in a three-necked flask at 50° C., and keep the temperature for reaction for 2 hours. After the reaction is completed, the temperature of the three-necked flask is raised to 85° C., and toluene is evaporated under reduced pressure to obtain modified 1-aminopyrene;
[0077] Weigh: 2.5 g of graphene, 2.5 g of modified 1-aminopyrene and 275 mL of ethanol, place them in a three-necked flask heated to 55°C, stir for 30 min, add 40 mL of 0.2 mol / L sodium hydroxide solution to the three-necked flask, keep warm and react for 90 min, after the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 80°C, and vacuum dry it to constant weight to obtain modified graphene;
[0078] Weigh: 125 mL of N,N-dimethylformamide, 1.5 g of modified graphene and 1.5 g of modified ferrosoferric oxide nanoparticles, place in a three-necked flask, heat to 105°C, ultrasonically disperse for 20 min, add 3.2 mol / L sodium hydroxide solution to adjust the pH to 8.01, and keep warm for 1 h. After the reaction, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry to constant weight to obtain a modified graphene composite.
[0079] S2. Preparation of modified polyurethane
[0080] Weigh: 25 mL of acetone and 0.25 g of dibutyltin dilaurate, put them in a three-necked flask, heat to 80°C, keep warm for 2 hours to obtain a catalyst solution, and set aside;
[0081] Weigh: 0.07 mL of 1-thioglycerol, 0.07 mL of tridecafluorooctyl methacrylate, 25 mL of acetone and 0.06 mL of dimethylphenylphosphine borane in a three-necked flask, heat to 60° C., and stir for 6 h to obtain a fluorine-containing monomer;
[0082] Weigh: 0.25 g of isophorone diisocyanate, 0.25 g of polyethylene glycol and 75 mL of acetone, put them into a round-bottom flask, ultrasonically disperse them for 50 min, add them dropwise into 25 mL of the catalyst solution, add 4.5 mL of the fluorinated monomer and 0.25 g of 2-hydroxyethyl disulfide, and react them at this temperature for 2 h to obtain a modified polyurethane.
[0083] S3. Preparation of modified crosslinking agent
[0084] Weigh: 250 mL of ethyl acetate and 250 mL of pure water, mix well to obtain ethyl acetate solution, set aside;
[0085] Weigh: Place 7.5 mL of polypropylene glycol, 15 mL of epichlorohydrin and 0.4 mL of boron trifluoride ether in a three-necked flask, heat to 60°C, stir for 3 h, add 50 mL of 1.5 mol / L sodium hydroxide solution and 40 mL of sodium hydroxide solution, keep warm and stir for 6 h, wait for the reaction liquid to cool to room temperature, extract with ethyl acetate solution 3 times, take the upper liquid and evaporate it at low pressure to obtain a modified cross-linking agent.
[0086] S4. Preparation of anti-drilling down jacket fabric
[0087] Weigh: 0.75 g of modified graphene composite, 3.5 g of modified polyurethane and 75 mL of N,N-dimethylformamide into a three-necked bottle, and ultrasonically disperse for 2 h to obtain a spinning solution for later use;
[0088] The spinning solution was placed in a 100 mL syringe after being allowed to stand to remove bubbles. A needle with an inner diameter of 0.75 mm and an outer diameter of 1 mm was selected as the spinning needle. Tin foil was attached to the drum as a receiving layer. The electrospinning voltage was set to 15 kV, the perfusion speed was set to 2 mL / h, the perfusion volume was set to 10 mL, the drum speed was set to 400 r / min, and the distance between the needle and the receiver was 12 cm. After the spinning was completed, the fabric lining film was obtained by drying.
[0089] The TC cloth is used as the outer layer, the fabric lining film is used as the inner layer, a modified cross-linking agent is coated between the two layers, and the layers are put into a hot-melt adhesive machine to obtain the down-penetration-proof down jacket fabric.
[0090] Example 3
[0091] This embodiment provides a processing technology for anti-drilling down jacket fabric, comprising the following steps:
[0092] S1. Preparation of modified graphene composite
[0093] Weigh: 3 g of ferroferric oxide nanoparticles, 60 mL of acetone and 1.5 g of KH-560 in a three-necked flask, incubate and disperse for 3 h, centrifuge, wash the precipitate with acetone for 3 times, dry to obtain modified ferroferric oxide nanoparticles, and set aside;
[0094] Weigh: Under nitrogen protection, place 300 mL of toluene, 2 g of 1-aminopyrene and 2 g of isocyanatopropyltriethylsilane in a three-necked flask at 50°C, keep warm for 2 hours, and after the reaction is completed, raise the temperature of the three-necked flask to 85°C, evaporate toluene under reduced pressure, and obtain modified 1-aminopyrene;
[0095] Weigh: 3 g of graphene, 5 g of modified 1-aminopyrene and 300 mL of ethanol, place them in a three-necked flask heated to 40°C, stir for 30 min, add 50 mL of 0.2 mol / L sodium hydroxide solution to the three-necked flask, keep warm and react for 90 min, after the reaction is completed, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 80°C, and vacuum dry it to constant weight to obtain modified graphene;
[0096] Weigh: 150 mL of N,N-dimethylformamide, 2 g of modified graphene and 2 g of modified ferrosoferric oxide nanoparticles, place in a three-necked flask, heat to 110°C, ultrasonically disperse for 20 min, add 3.5 mol / L sodium hydroxide solution to adjust the pH to 8.02, and keep warm for 1 h. After the reaction, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 80°C, and vacuum dry to constant weight to obtain a modified graphene composite.
[0097] S2. Preparation of modified polyurethane
[0098] Weigh: 30 mL of acetone and 0.5 g of dibutyltin dilaurate, put them in a three-necked flask, heat to 80°C, keep warm for 2 hours to obtain a catalyst solution, and set aside;
[0099] Weigh: 0.1 mL of 1-thioglycerol, 0.1 mL of tridecafluorooctyl methacrylate, 30 mL of acetone and 0.1 mL of dimethylphenylphosphine borane into a three-necked flask, heat to 60° C., and stir for 6 h to obtain a fluorine-containing monomer;
[0100] Weigh: 0.5 g of isophorone diisocyanate, 0.5 g of polyethylene glycol and 100 mL of acetone, put them in a round-bottom flask, ultrasonically disperse them for 50 min, add them dropwise into 30 mL of the catalyst solution, add 5 mL of the fluorinated monomer and 0.5 g of 2-hydroxyethyl disulfide, keep the temperature for reaction for 2 h, and obtain a modified polyurethane.
[0101] S3. Preparation of modified crosslinking agent
[0102] Weigh: 300 mL of ethyl acetate and 300 mL of pure water, mix well to obtain ethyl acetate solution, set aside;
[0103] Weigh: place 10 mL of polypropylene glycol, 20 mL of epichlorohydrin and 0.5 mL of boron trifluoride ether in a three-necked flask, heat to 60°C, stir for 3 h, add 60 mL of 2 moL / L sodium hydroxide solution, keep warm and stir for 6 h, wait for the reaction liquid to cool to room temperature, extract with ethyl acetate solution 3 times, take the upper liquid and evaporate it at low pressure to obtain a modified cross-linking agent.
[0104] S4. Preparation of anti-drilling down jacket fabric
[0105] Weigh: 1 g of modified graphene composite, 5 g of modified polyurethane and 100 mL of N,N-dimethylformamide into a three-necked bottle, and perform ultrasonic dispersion for 2 h to obtain a spinning solution for later use;
[0106] The spinning solution was placed in a 100 mL syringe after being allowed to stand to remove bubbles. A needle with an inner diameter of 0.75 mm and an outer diameter of 1 mm was selected as the spinning needle. Tin foil was attached to the drum as a receiving layer. The electrospinning voltage was set to 15 kV, the perfusion speed was set to 2 mL / h, the perfusion volume was set to 10 mL, the drum speed was set to 400 r / min, and the distance between the needle and the receiver was 12 cm. After the spinning was completed, the fabric lining film was obtained by drying.
[0107] The TC cloth is used as the outer layer, the fabric lining film is used as the inner layer, and a modified cross-linking agent is coated between the two layers to obtain the down drilling-proof down jacket fabric.
[0108] Comparative Example 1
[0109] The difference between this comparative example and Example 3 is that the step of modifying the ferrosoferric oxide nanoparticles in step S1 is eliminated, and an equal amount of silicon dioxide nanoparticles are used to replace the modified ferrosoferric oxide nanoparticles in the process of preparing the modified graphene composite.
[0110] Comparative Example 2
[0111] The difference between this comparative example and Example 3 is that the step of preparing the fluorine-containing monomer in step S2 is eliminated, and 1-thioglycerol is used in an equal amount to replace the fluorine-containing monomer in the process of preparing the modified polyurethane.
[0112] Comparative Example 3
[0113] The difference between this comparative example and Example 3 is that the use of the modified cross-linking agent in preparing the spinning solution in step S4 is eliminated, and the modified cross-linking agent is not coated between the inner and outer layers during thermal bonding.
[0114] Performance Test:
[0115] The breaking strength of the anti-drilling down jacket fabrics prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 3923.2-2013 "Tensile properties of textile fabrics - Part 2: Determination of breaking strength (grab method)";
[0116] The waterproofness of the anti-drilling down jacket fabrics prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 4744-2013 "Testing and evaluating the waterproof performance of textiles - Hydrostatic pressure method";
[0117] The air permeability of the anti-down jacket fabrics prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 5453-1997 "Determination of air permeability of textile fabrics";
[0118] The antistatic properties of the anti-drilling down jacket fabrics prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 12703.4-2010 "Evaluation of electrostatic properties of textiles Part 4: Resistivity";
[0119] With reference to the standard GB / T 12705.1-2024 “Test method for anti-down drilling of textiles Part 1: Friction method”, the anti-down drilling properties of the anti-down drilling down jacket fabrics prepared in Examples 1-3 and Comparative Examples 1-3 were tested, and the specific data are shown in Table 1.
[0120] Table 1. Performance test data of samples
[0121] Project Category Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Breaking strength / N 200 211 205 175 180 156 Hydrostatic pressure resistance grade / level 4 5 4 2 3 4 <![CDATA[Air permeability / mm·s -1 > 0.451 0.532 0.482 0.449 0.423 0.411 Resistivity / Ω·cm 0.582 0.535 0.586 0.710 0.540 0.619 Number of drill piles / root 7 4 8 20 12 22
[0122] Data Analysis:
[0123] Comparative analysis of the data of Examples 1-3 and Comparative Examples 1-3 shows that the breaking strength of the anti-drilling down jacket fabric prepared by the present invention reaches 211N, the hydrostatic pressure resistance level reaches level 5, and the air permeability is 0.532mm·s -1 , the resistivity is 0.535Ω·cm and the number of down drilling roots is 4, indicating that the anti-down drilling down jacket fabric prepared by the present invention has good anti-down drilling performance, waterproof air permeability, mechanical properties and antistatic properties;
[0124] The flame retardant performance of Comparative Example 1 is substantially the same as the air permeability of Examples 1-3, and its breaking strength, hydrostatic pressure resistance and resistivity decrease, and the number of down piles increases, indicating that in the process of preparing the modified graphene composite, adding modified ferroferric oxide nanoparticles can improve the dispersibility of the modified graphene composite in the spinning solution, thereby improving the down-proof performance, waterproof performance, mechanical performance and antistatic performance of the down-proof down jacket fabric;
[0125] The breaking strength and hydrostatic pressure resistance of Comparative Example 2 decreased, and the number of down drilling roots increased, which was lower than that of Examples 1-3, indicating that the modified polyurethane prepared using fluorine-containing monomers can improve the waterproof performance, mechanical properties and anti-down drilling performance of anti-down drilling down jacket fabrics;
[0126] The breaking strength, hydrostatic pressure resistance and resistivity of Comparative Example 3 decreased, and the number of down roots increased, indicating that the modified cross-linking agent can improve the anti-down drilling performance, waterproof breathability, mechanical properties and antistatic properties of the anti-down drilling down jacket fabric;
[0127] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A processing technology for anti-drilling down jacket fabric, characterized in that: The steps include: S1. Under nitrogen protection, place isocyanate propyl triethylsilane, toluene and 1-aminopyrene in a three-necked flask at a temperature of 50-60°C, keep the temperature for reaction for 1-2 hours, and then post-treat to obtain modified 1-aminopyrene; S2, placing graphene, modified 1-aminopyrene and ethanol in a three-necked flask heated to 50-60°C, stirring for 20-30 minutes, adding sodium hydroxide solution to the three-necked flask, keeping the temperature for reaction for 90-120 minutes, post-treating, and obtaining modified graphene; S3, placing N,N-dimethylformamide, modified graphene and modified ferroferric oxide nanoparticles in a three-necked flask, heating to 100-110°C, ultrasonically dispersing for 20-30 minutes, adding sodium hydroxide solution to adjust the pH to 8±0.2, keeping the temperature for reaction for 0.5-1 hour, and post-treating to obtain a modified graphene composite; S4, placing the modified graphene composite, modified polyurethane and N,N-dimethylformamide in a three-necked flask, ultrasonically dispersing for 1-2 hours, and electrospinning to obtain a fabric lining film; S5. The base fabric is used as the outer layer and the fabric lining film is used as the inner layer. A modified cross-linking agent is coated between the two layers, and the layers are placed in a hot melt bonding machine for thermal bonding to obtain a down-proof down jacket fabric.
2. The processing technology of the anti-down drilling down jacket fabric according to claim 1 is characterized in that: In step S1, the amount ratio of isocyanatepropyltriethylsilane, toluene and 1-aminopyrene is 1-2g:250-300mL:1-2g; in step S2, the concentration of the sodium hydroxide solution is 0.1-0.2mol / L, and the amount ratio of the graphene, modified 1-aminopyrene, ethanol and sodium hydroxide solution is 2-3g:1-5g:250-300mL:30-50mL; in step S3, the concentration of the sodium hydroxide solution is 3-3.5mol / L, the N,N-dimethylformamide, modified graphite The dosage ratio of graphene and modified ferroferric oxide nanoparticles is 100-150mL:1-2g:1-2g; in step S4, the dosage ratio of the modified graphene composite, modified polyurethane and N,N-dimethylformamide is 0.5-1g:2-5g:50-100mL; in step S5, the base fabric is composed of nylon fiber and cotton fiber blended in a blending ratio of 20-30:70-80, the hot pressing process temperature of thermal bonding is 120-150°C, the hot pressing time is 30-40S, and the hot pressing pressure is 1.5-2.0MPa.
3. The processing technology of the anti-down drilling down jacket fabric according to claim 1 is characterized in that: The preparation method of the modified ferroferric oxide nanoparticles is as follows: placing ferroferric oxide nanoparticles, acetone and KH-560 in a three-necked flask, heat-insulating and dispersing for 3-4 hours, centrifuging, washing the precipitate with acetone for 2-3 times, and drying to obtain the modified ferroferric oxide nanoparticles.
4. The processing technology of the anti-down drilling down jacket fabric according to claim 3 is characterized in that: The usage ratio of the modified ferrosoferric oxide nanoparticles, acetone and KH-560 is 2-3 g: 50-60 mL: 0.5-1 g.
5. The processing technology of the anti-down drilling down jacket fabric according to claim 1 is characterized in that: The preparation method of the modified polyurethane comprises the following steps: A1. Place acetone and dibutyltin dilaurate in a three-necked flask, heat to 70-80°C, and keep the temperature for reaction for 1-2 hours to obtain a catalyst solution for later use; A2, 1-thioglycerol, tridecafluorooctyl methacrylate, acetone and dimethylphenylphosphine borane are placed in a three-necked flask, heated to 50-60°C, and stirred for 5-6 hours to obtain a fluorine-containing monomer; A3. Place isophorone diisocyanate, polyethylene glycol and acetone in a round-bottom flask, disperse them by ultrasonic for 30-60 minutes, add them dropwise to the catalyst solution, add fluorinated monomer and 2-hydroxyethyl disulfide, and react at the temperature for 2-3 hours to obtain modified polyurethane.
6. The processing technology of the anti-down drilling down jacket fabric according to claim 5 is characterized in that: In step A1, the amount ratio of acetone to dibutyltin dilaurate is 20-30mL:0.1-0.5g; in step A2, the volume ratio of 1-thioglycerol, tridecafluorooctyl methacrylate, acetone and dimethylphenylphosphine borane is 0.05-0.1:0.05-0.1:20-30:0.05-0.1; in step A3, the amount ratio of isophorone diisocyanate, polyethylene glycol, acetone, catalyst solution, fluorine-containing monomer and 2-hydroxyethyl disulfide is 0.1-0.5g:0.1-0.5g:50-100mL:20-30mL:2-5mL:0.1-0.5g.
7. The processing technology of the anti-down drilling down jacket fabric according to claim 1 is characterized in that: The preparation method of the modified crosslinking agent comprises the following steps: placing polypropylene glycol, epichlorohydrin and boron trifluoride etherate in a three-necked flask, heating to 50-60° C., stirring for 2-5 hours, adding sodium hydroxide solution, keeping the temperature and stirring for 2-6 hours, and post-processing to obtain the modified crosslinking agent.
8. The processing technology of the anti-down drilling down jacket fabric according to claim 7 is characterized in that: The volume ratio of the polypropylene glycol, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution is 5-10:10-20:0.3-0.5:40-60mL, and the concentration of the sodium hydroxide solution is 1.5-2mol / L.
Citation Information
Patent Citations
Moisture-absorption breathable heat-preservation down feather composite fabric and preparation method thereof
CN115246259A
Breathable down-proof fabric and preparation method thereof
CN115613352A
Water-repellent down manufacturing method and its product thereof
TW201612373A
Process for producing fabric of continuous graphene fiber yarns from functionalized graphene sheets
US20190352806A1
Fabric of continuous graphene fiber yarns from functionalized graphene sheets
WO2019226513A1
Cited By
High-permeability down jacket fabric and preparation process thereof
CN120138998A
Ultrahigh down-proof down jacket fabric and preparation process thereof
CN120287697A